Advances in desmuramyl peptide research - Ribić, Rosana (Array, 2019)
Immune adjuvants are added to vaccines in order to enhance the immune response to an antigen. Muramyl dipeptide, N-acetylmuramyl-L-alanyl-D-isoglutamine, is the smallest structural unit of peptidoglycans showing the immunostimulating activity. Muramyl dipeptide analogues without the hydrophilic N-acetylmuramyl moiety are called desmuramyl peptides. Here, we provide review of desmuramyl peptides which were synthesized in order to improve the pharmacological properties of parent muramyl dipeptide, including our results regarding adamantane containing derivatives. Approach for future design of novel immunostimulators based on multiple pathogen recognition receptor activation was also considered.